A comparative performance analysis among Hybrid NOMA Schemes for 5th Generation (5G) and beyond Wireless Communications - Bal, Anindya; Nuhi, Jannatul Ferdous Chowdhury; Sur, Mousumi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.